Does Viewing a Picture of a Pet During a Mental Arithmetic Task Lower Stress Levels?. (4th July 2019) - Ein, Natalie; Hadad, Marilyn; Reed, Maureen J.; Vickers, Kristin
ABSTRACT: Pets can reduce stress in their owner; however, they are not always permitted in public and institutional places. This study examined the impact of people viewing a picture of their pet versus other images on stress levels. One hundred and twenty participants were randomly assigned to one of six conditions. These involved completing a mental arithmetic task while viewing a picture of either their personal pet; an unfamiliar animal; a familiar, supportive person; a stranger; a pleasant image of nature; or no image. Stress was measured through subjective and physiological methods. For participants, viewing a picture of their pet did not reduce their stress response to the task, while viewing a picture of a familiar, supportive person increased the stress response, relative to the controls. Post-stressor, participants in the personal-pet condition rated the picture as making them feel more relaxed, compared with the other conditions. Active interaction with a pet may be required to reduce stress.